2022
DOI: 10.1098/rsif.2022.0131
|View full text |Cite
|
Sign up to set email alerts
|

Charting the twist-to-bend ratio of plant axes

Abstract: During the evolution of land plants many body plans have been developed. Differences in the cross-sectional geometry and tissue pattern of plant axes influence their flexural rigidity, torsional rigidity and the ratio of both of these rigidities, the so-called twist-to-bend ratio. For comparison, we have designed artificial cross-sections with various cross-sectional geometries and patterns of vascular bundles, collenchyma or sclerenchyma strands, but fixed percentages for these tissues. Our mathematical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…With regard to the practice of Baubotanik, inosculations and branch junctions can be deduced to be anatomically comparable to a high degree if the common growth rings dominate the structure. Wolff–Vorbeck et al [ 45 ] have shown that the flexural rigidity and the torsional rigidity, both mechanical properties in the linear-elastic range, are largely determined by the cross-sectional patterns of the involved tissues. Since the tissue distributions are remarkably similar for inosculation and branch junction, we can assume that the flexural rigidity and the torsional rigidity are also comparable.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the practice of Baubotanik, inosculations and branch junctions can be deduced to be anatomically comparable to a high degree if the common growth rings dominate the structure. Wolff–Vorbeck et al [ 45 ] have shown that the flexural rigidity and the torsional rigidity, both mechanical properties in the linear-elastic range, are largely determined by the cross-sectional patterns of the involved tissues. Since the tissue distributions are remarkably similar for inosculation and branch junction, we can assume that the flexural rigidity and the torsional rigidity are also comparable.…”
Section: Discussionmentioning
confidence: 99%
“…The high correlations between LIA i and ΔLIA max may be due to the relative stiffness of the petiole (Filartiga et al, 2022; Niklas, 1999; Wolff‐Vorbeck et al, 2022). A less stiff petiole would result in a larger LIA i as well as a larger maximum change.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf vibration may cause leaf surface storage to vary depending on individual rainfall characteristics, such as raindrop‐size distribution, acceleration and velocity of falling raindrops, and raindrop impact frequency (Konrad et al, 2021; Lauderbaugh & Holder, 2022). The degree to which leaves move following impact from the momentum of a falling raindrop is primarily influenced by species‐specific, biomechanical properties of the leaf, such as material composition, morphology, and stiffness (Lauderbaugh & Holder, 2022; Roth‐Nebelsick et al, 2022; Wolff‐Vorbeck et al, 2022). Hydrophobic properties of the leaf surface may also influence the degree to which water drops shed from the leaf surface (Holder, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These measurements associated with the anatomical study of the tissues could allow a better understanding of the mechanism at the origin of the rigidification dynamics at all points of the searcher shoots. The anatomical organizations in the mechanical and postural life-histories of plants are potentially embracing ecology, biomechanics and robotics [ 36 ].…”
Section: Discussionmentioning
confidence: 99%